The Influence of Love of Money, Machiavellianism, and Idealism on the Ethical Perceptions of Accounting Students - Ulum, Fahmy; Sari, Rida Perwita (Transpublika Publisher, 2025)
This study focuses on how three psychological characters, Love of Money, Machiavellianism, and Idealism, influence how Accounting students at UPN ‘Veteran’ East Java view ethics. The respondents in this study were 87 students from the 2021-2022 cohort who had completed the Business and Professional Ethics course. Information was gathered by administering a survey with a measurement scale and then examined using the PLS-SEM method through the use of the SmartPLS software. The outcomes were rather intriguing: firstly, it was discovered that the love of money has a considerable impact on the ethical viewpoints of students (t-statistic = 3.946; p<0.001). Secondly, Machiavellian attributes were also determined to have a significant effect (t-statistic = 3.497; p = 0.001). However, the same could not be said for Idealism, as it did not demonstrate a notable impact (t-statistic = 0.170; p = 0.865). These discoveries could offer valuable insights for enhancing ethics-related teachings in accounting studies. Specifically, the teaching materials focusing on attitudes towards wealth and manipulative behaviours should be given more emphasis in shaping the ethical comprehension of aspiring accountants.